2008
DOI: 10.4103/0970-1591.40622
|View full text |Cite
|
Sign up to set email alerts
|

Acute postoperative complications of hypospadias repair

Abstract: PurposeComplications in hypospadias surgery are higher than other reconstructive procedures. The incidence of complications can be reduced if proper preventive measures are taken. The review aims to highlight incidences, causes, and preventive measures of acute complications of hypospadias repair.Materials and MethodsLiterature reports were reviewed in Pubmed by giving the key word acute complications of hypospadias repair, wound infection, wound dehiscence, flap necrosis, edema, penile torsion, urethral fistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 44 publications
3
76
1
2
Order By: Relevance
“…The aim of hypospadias repair is to achieve normal urinary and sexual function with good esthetic result and self-confidence of the child. 2 Perioperative and postoperative antibiotics are widely used by pediatric urologists, particularly in hypospadias surgery. 3 The rationale was to reduce the risk of urinary tract infection (UTI) in the early postoperative period following the placement of a catheter, [4][5][6][7][8] Moreover, antibiotics were effective at reducing the risk of meatal stenosis and fistula.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of hypospadias repair is to achieve normal urinary and sexual function with good esthetic result and self-confidence of the child. 2 Perioperative and postoperative antibiotics are widely used by pediatric urologists, particularly in hypospadias surgery. 3 The rationale was to reduce the risk of urinary tract infection (UTI) in the early postoperative period following the placement of a catheter, [4][5][6][7][8] Moreover, antibiotics were effective at reducing the risk of meatal stenosis and fistula.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative edema was not observed in any of our cases. Bhat and Mandal [10] found that edema was the second most common early complication after hypospadias surgery. Urethro-cutaneous fistula remains the most common complication encountered by all.…”
Section: Discussionmentioning
confidence: 99%
“…Acute complications include bleeding, hematoma, oedema, infection, wound dehiscence, skin or flap necrosis, fistula, penile torsion, penile erection, inadvertent removal of urethral stent and bladder spasm [3]. Chronic complications can be classified as occurring in the skin or penile shaft, urethral, glanular and other.…”
Section: Discussionmentioning
confidence: 99%
“…Balanitis xerotica obliterans, meatal stenosis, prolapsus, retraction, tissue defect, glans necrosis, glans dehiscence, figure distractions are the reported complications of glans penis. Other complications are vesicosphincteric dyssynergy, bad cosmesis and urinary flow disorders [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%